Vortex Magnetic Domain State Behavior in the Day Plot - Williams, Wyn (2024)
The ability of rocks to hold a reliable record of the ancient geomagnetic field depends on the structure and stability of magnetic domain‐states contained within constituent particles. In paleomagnetic studies, the Day plot is an easily constructed graph of magnetic hysteresis parameters that is frequently used to estimate the likely magnetic recording stability of samples. Often samples plot in the region of the Day plot attributed to so‐called pseudo‐single‐domain particles with little understanding of the implications for domain‐ states or recording fidelity. Here we use micromagnetic models to explore the hysteresis parameters of magnetite particles with idealized prolate and oblate truncated‐octahedral geometries containing single domain (SD), single‐vortex and occasionally multi‐vortex states. We show that these domain states exhibit a well‐ defined trend in the Day plot that extends from the SD region well into the multi‐domain region, all of which are likely to be stable remanence carriers. We suggest that although the interpretation of the Day plot and its variants might be subject to ambiguities, if the magnetic mineralogy is known, it can still provide some useful insights about paleomagnetic specimens' dominant domain state, average particle sizes and, consequently, their paleomagnetic stability.